Development Of Credit Shopping Application To Support Synergy Between Sharia Cooperatives - Sjamsuridjal; Soleh Sabarudin (Jurnal Mantik, 2021)
The background for the development of the shopping system on credit stems shopping from a long study of distribution channels from producers to consumers as well as the proliferation of mini-markets and online shoops, causing several problems faced by traders and small producers. The system developed in this study aims to support synergies between sharia cooperatives, small traders, and small producers in transactions with consumers. There are three things that are produced in this research, namely: 1) The concept of a murabahah shopping system which is designed to involve sharia cooperatives, traders, producers and consumers, 2) Synergy design between sharia cooperatives, traders, producers and consumers so that economic interaction occurs to work together filling and completing deficiencies so that they can produce optimum economic activity, and 3) Application of the murabahah shopping system to support synergies between sharia cooperatives, producers, traders and consumers. The murabahah shopping system application consists of five sub-systems, namely the merchant sub-system, the producer sub-system, the consumer sub-system, the cooperative sub-system, and the system management sub-system. This research was conducted in a descriptive qualitative manner with literature review methodology and observations related to the title of this study. Programming in this study uses object-oriented programming methods, and is done with PHP software based on windows and web and the data base used is MySQL. The results of the analysis and design that have been compiled are written in the form of architectural designs, use case diagrams, activity diagrams, procedures and menu structures that are used as guidelines in programming implementation. The programming of this murabahah shopping system application has been completed which is then ready to be implemented in traders, producers, cooperatives and their members.